Two UGT84A Family Glycosyltransferases Regulate Phenol, Flavonoid, and Tannin Metabolism in Juglans regia (English Walnut) - Saxe, Houston J.; Horibe, Takanori; Balan, Bipin; Butterfield, Timothy S.; Feinberg, Noah G.; Zabaneh, Christopher M.; Jacobson, Aaron E.; Dandekar, Abhaya M. (Frontiers in Plant Science, 2021)
We showed previously that gallic acid is produced in walnut from 3-dehydroshikimate by a shikimate dehydrogenase (JrSkDH). This study focuses on the next step in the hydrolysable tannin pathway, the formation of 1-Ο-galloyl-β-D-glucose from the phenolic gallic acid and UDP glucose by a glycosyltransferase. JrGGT1 (UGT84A73) and JrGGT2 (UGT84A74) are predicted to be two such glycosyltransferases, which we expressed in tobacco plants. GC-MS analysis of the transgenic tobacco revealed moderate, yet significant alterations in plant secondary metabolism, such as depleted phenolic acids, including gallic acid. We postulate that these effects are due to JrGGT1 and JrGGT2 activity, as JrGGT orthologs glycosylate these phenolic compounds in vitro. Moreover, JrGGT expression in tobacco caused upregulation of shikimic acid pathway metabolites and differing responses in phenylpropanoids, such as phenolic acids and flavonoids. In transcriptome analysis of walnut pellicle tissues, both JrGGTs showed substantial and significant expression correlations with the gallic acid-producing JrSkDHs and were highly coexpressed with the genetic circuits constituting the shikimic acid and phenylpropanoid biosynthetic pathways. Verification of JrGGT gene expression by transcriptome analysis of 20 walnut tissues revealed striking similarities with that of the pellicle data, with the greatest expression in roots, wood, buds, and leaves of Juglans regia cv. Chandler: tissues that typically accumulate hydrolysable tannins. Like the transgenic tobacco, pellicle metabolomic analyses revealed that many phenylpropanoids correlated significantly and negatively with JrGGT expression, while shikimic acid pathway metabolites correlated significantly and positively with JrGGT expression. This research supports the hypothesis that JrGGT1 and JrGGT2 play nontrivial roles in metabolism of phenolic acids, flavonoids, and ostensibly, tannins.